Students Abstract Thinking Abilities in terms of Mathematical Disposition - Nurrahmah, Arfatin; Agustina, Lasia; Nurhayati, Nurhayati (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research aims to describe students abstract thinking abilities in the probability theory course in terms of mathematical disposition. The research method used is descriptive research with a qualitative approach. The research subjects were 5th-semester students who took probability theory courses. Determination of subjects using purposive sampling techniques. Instruments used include test results of mathematical abstract thinking abilities, disposition questionnaires, interview guidelines, and researchers as the key instruments. Analysis data using the Miles model and Huberman includes data reduction, display data and conclusion drawing/verification. The research results are, Subject 1 (S1) is in the high mathematical disposition category, fulfills three indicators of abstract thinking abilities, namely transforming problems into symbols, manipulation process of abstract mathematical objects, and the formation of mathematical concepts related to other concepts. Subject 2 (S2) is in the medium mathematical disposition category, fulfilling two indicators of abstract thinking abilities, namely transforming problems into symbols and the manipulation process of abstract mathematical objects, the formation of mathematical concepts related to other concepts. Subject 3 (S3) is in the low mathematical disposition category, it only fulfills one indicator of the abstract thinking abilities, namely transforming problems into symbols.